RNA-dependent DNA polymerase activity in cauliflower mosaic virus-infected plant leaves - Volovitch, M. (1984)
Cauliflower mosaic virus (CaMV) is a plant DNA with an 8-kb circular double-stranded genome. CaMV-specific DNA and RNA molecules present in infected Brassica cells share some structural features with DNAs and RNAs of retroviruses and hepatitis B virus. This led to the hypothesis that CaMV replication occurs via reverse transcription of an RNA intermediate. Here we report the first characterization of a new DNA polymerase activity, specific to CaMV-infected tissues. A subcellular fraction of infected cells shows capacity to copy poly(C) and the heteropolymeric regions of natural mRNAs. Chromatographic isolation of the poly(C)-dependent activity clearly establishes that it is distinct from the classical γ-like DNA polymerases previously described in plant cells. The significant homology observed between defined regions of the Moloney murine leukemia virus (MMLV) polymerase and CaMV unassigned gene V product favours the idea that the reverse transcriptase-like DNA polymerase detected in infected cells is a virus-encoded enzyme.